Social Media and Politeness in Adolescent Language Practices: A Sociolinguistic Perspective - Dery Saefudin; Prima Santosa; Kartono Kartono; Siti Nurani; Shadam Pratama (SALEE: Study of Applied Linguistics and English Education, 2026)
This study aims to analyze the relationship between social media use and language politeness among students at SMP N 222 East Jakarta, considering that social media serves as a socialization space that influences teenagers’ linguistic interactions. The study uses a quantitative approach with a correlational design and involves 180 students from grades 7 to 9. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and Spearman’s non-parametric correlation test because one of the variables was not normally distributed. The results show that students have a fairly high level of social media use (M = 3.5406) and a high level of language politeness (M = 4.2044). The Spearman correlation test revealed a weak but significant positive relationship between social media use and language politeness (r = 0.209, p = 0.005), indicating that the more students engage with social media, the more likely their language politeness increases, although the effect is small. These findings confirm that social media can function as a social space supporting polite linguistic behavior. The implication for education is the need for digital literacy and supervision of online interactions by schools and parents to guide teenagers’ language behavior in a positive way.